Smoke and Mirrors : Infrastructure State-Owned Enterprises and Fiscal Risks - Herrera Dappe, Matias; Musacchio, Aldo; Pan, Carolina; Semikolenova, Yadviga Viktorivna; Turkgulu, Burak; Barboza, Jonathan (Washington, DC: World Bank, 2022)
Infrastructure is critical to economic development. When infrastructure companies are owned and operated by the government, however, they create significant sources of fiscal risk. These fiscal risks can be sizable, but they are often preventable with proper planning, risk assessment, and strict rules and procedures for corporate and fiscal governance. This paper examines fiscal risk stemming from state-owned enterprises (SOEs) in the infrastructure sector in a sample of 135 firms in 19 countries from an original database of SOE financials for 2009–18. The paper develops a typology of fiscal risks and their determinants, builds new measures of fiscal injections to SOEs, and documents them using the novel database. The results show that governments support SOEs through a remarkably wide range of fiscal instruments. The fiscal cost of supporting infrastructure SOEs is usually below 1 percent of gross domestic product. Support is more prevalent and frequent than previously thought. The findings show that fiscal risk stems not only from “tail risk,” but also from the everyday operation of infrastructure SOEs. The paper calculates the Altman Z” score (a measure of default risk) and shows that it can be used to forecast the need for fiscal injections in SOEs.